Clinical presentation and management of nasolabial cyst-a case report - Khatri, Rajkumari P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Nasolabial cysts are rare, non-odontogenic, soft-tissue cysts that develop between the upper lip and nasal vestibule with an overall incidence of 0.7% out of all maxillofacial cysts. This lesion grows slowly and measures 1 to 5 cm in diameter. Its pathogenesis is uncertain. A cyst that erodes the surface of the maxilla is named nasoalveolar cyst. The predominant presentation of a nasolabial cyst is a painless localized swelling with varying degrees of nasal obstruction, facial asymmetry. Several treatment modalities have been described in the management of the nasolabial cyst. In this paper, we present a case of a nasolabial cyst in a 45-year- female patient that slowly increased in size over a period of 2 years, with associated mild pain and nasal obstruction, and increased rapidly in size since 2 months causing gross facial asymmetry. It had caused a mass effect upon the maxilla, resulting in scalloping. The cyst was excised entirely with no evidence of recurrence at the 9 months follow up. The nasolabial cyst is a rare soft-tissue non-odontogenic cyst. Complete surgical excision using an open approach performed with no recurrence but she developed inferior orbital neuralgia 1 month after surgery which was managed successfully by conservative management with steroids and gabapentin.